SPECTROSCOPY AND STRUCTURE OF HIBONITE, GROSSITE, AND CAAL2 O4: IMPLICATIONS FOR ASTRONOMICAL ENVIRONMENTS - Hofmeister A.M.; Wopenka B.; Locock A.J. (My University, 2004)
Infrared (IR) spectra of phases found in calcium-aluminum rich inclusions in meteorites are incomplete, yet such data are needed to ascertain the mineralogy of astronomical environments. To better characterize the system CaO-Al2O3, we obtained IR thin-film absorption data, partially polarized Raman scattering spectra, and single-crystal X-ray structure refinements from small single-crystals of end-member hibonite (CaAl12O19) and grossite (CaAl4O7), synthesized by laser-heating. Vibrational spectra were also acquired from natural samples of Th-bearing hibonite, synthetic corundum (Al2O3), 17O-enriched grossite, CaAl2O4, and CaO. Spectral fitting provided band positions and widths. The true absorbance of strong IR peaks in calcium aluminates is 1–2/μm, based on thickness determined from interference fringes and on comparison with absorption coefficients calculated from reflectivity data on natural hibonite. Our data on the lattice vibrations of hibonite reveal that the terrestrial samples are partially metamict: their spectra cannot be used for comparison with astronomical objects because of peak broadening and changes in the polarization of the vibrations. null Direct comparison of our IR data of synthetic samples with astronomical observations shows that grossite and hibonite are present in the proto-planetary nebula NGC 6302. That spectral patterns match provides a strong case. Corundum, spinel, and melilite-group minerals also could be present in the nebula. Because spectra of melilites resemble those of pyroxenes, the latter assignment is less certain. We limit our compositional analysis of the nebula to matching spectral patterns, because detailed spectral modeling of the mineralogy would be both premature (due to a lack of cryogenic IR data), and uncertain (due to the occurrence of dust in clumps large enough to emit as blackbodies). The inferred mineralogy of NGC 6302 follows the condensation sequence for a nebula of solar composition, and contains mineral types known to be presolar.
Keywords: hibonite; grossite; CaAl2O4